Analisis Dampak Ekonomi Program Pengembangan Usaha Agribisnis Pedesaan (PUAP) Dalam Pengentasan Kemiskinan : Studi Kasus Gapoktan “Karunia” Desa Pringgasela, Kabupaten Lombok Timur - Tati Atmayanti; Mimi Cahayani (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2019)
The Rural Agribusiness Development Program (PUAP) is one of the poverty alleviation programs through agribusiness activities (agriculture sector) that has been implemented by the Gapoktan "Karunia" in Pringgasela Village, Pringgasela District, East Lombok Regency, which was formed in 2008 and started to receive PUAP program funding in the year 2010. The problem faced in relation to the sustainability of the program is the lack of optimal implementation of PUAP activities, especially in the field of agribusiness. The purpose of this study was to determine the economic impact of the PUAP Program in poverty alleviation of farmer group members in Pringgasela Village, East Lombok Regency. This type of research is a case study with a qualitative approach. Data collection techniques are done by observation and interview methods. Determination of informants using purposive sampling method from 62 people who are members of the Gapoktan "Gift". Data validation using source triangulation method, while data analysis techniques using interactive analysis methods. The findings in this study are the role of Gapoktan as an institution for implementing PUAP farmers is needed, an increase in farmers' income and ease in getting loans, farmers are expected to be able to improve their quality of life through efforts to develop the capabilities and skills of human resources (farmers), increase business scale and create efficiency in its activities, which in turn is able to increase its productivity. In addition, it is necessary to conduct more intensive counseling by the mentors to achieve the optimal PUAP program objectives.